The contribution of digital influencers to enhancing healthy nutritional awareness among consumers - Nacer, Khene Mohamed; Sabrina, Menani; Abdelrazak, Arif (The International tax journal, 2026)
This study aims to analyze the role of digital influencers on social media platforms in enhancing healthy nutritional awareness among consumers, in light of the widespread dissemination of nutrition and health content on platforms such as Instagram, YouTube, and Facebook. The study adopted the descriptive-analytical approach. The study observed a disparity in the credibility of content provided by some influencers who offer health advice without a scientific background or professional qualification. One of the study’s findings is that nutrition specialists are responsible for planning appropriate healthy dietary regimens, and it should be recognized that there is no single diet that applies to everyone. Daily nutritional needs vary from one individual to another due to differences in height, age, weight, and physical activity, as well as health, social, and psychological factors. The study also emphasizes the importance of obtaining information from reliable sources and receiving nutritional advice from qualified nutrition specialists. The study recommended encouraging partnerships between influencers and nutrition experts, as well as launching organized digital awareness campaigns in cooperation with official health institutions.